3 - Protest Movements and Social Media: Morocco’s February 20 Movement - Radi, Abdelaziz (Africa Development, 2017)
Historically, Morocco experienced large-scale political repression during the 1970s through the early 1990s. Through its actions, the regime repressed any claims aimed at challenging its authoritarian configuration of public space. Ironically, with the emergence of the ‘February 20’ movement, those claims were brought back again on to the political agenda. Born in the context of the Arab Spring, February 20 acquired legitimacy both nationally and regionally. Its use of civic and political forms of expression in order to conquer the social arena reflects not only a certain inefficiency of traditional representative bodies (political parties, official media and parliament) but also a relative emergency to convey their message. The leading technological means of communication used by the movement are Facebook, YouTube, Twitter, and blogs. The young used these tools not only to promote the movement per se, but also to facilitate its operational organization by informing policy makers, activists and even supporters of the movement nation-wide. This article tries to assess the extent to which the social media platforms utilized by the February 20 movement were a political game changer for a generation eager for freedom and change after decades of oppression in Morocco.